ANALISIS PENCANTUMAN KLAUSULA EKSONERASI DALAM PERJANJIAN PENYERAHAN ANAK ASUH KEPADA PANTI ASUHAN (SUATU PENELITIAN PADA PANTI ASUHAN ANAK YATIM MUHAMMADIYAH CABANG GANDAPURA KABUPATEN BIREUEN, ACEH) - NIA WINATA (PREMISE LAW JURNAL, 2015)
A child is a valuable blessing grace for a family, but a child sometimes becomes a financial burden for his parents/guardians since they cannot afford to support the life and the education of the child. Therefore, they are motivated to send the child to an orphanage. The result of the research showed that the implementation of the contract of handing over a child to Panti Asuhan Anak Yatim Muhammadiyah Cabang Gandapura, Bireuen, was done through a contract of handing over a child which consisted of minutes of the handing over and the statement from the parents or guardians which had been prepared by the management of the orphanage. The position of the exoneration clause in the contract, according to the Islamic Law and the Civil Law, is made on the agreement of the parties involved in the contract which binding and conclusive. An exoneration clause in a contract of handing over a child is only limited to the period of guidance, and it does not cause the broken off between the child and his parents or guardians. Keywords: Contract of Handing Over a Child, Exoneration Clause